2015
DOI: 10.1002/2015ja021752
|View full text |Cite
|
Sign up to set email alerts
|

Toward more reliable long‐term indices of geomagnetic activity: Correcting a new inhomogeneity problem in early geomagnetic data

Abstract: For the time before the space era, our knowledge of the centennial evolution of solar wind (SW) and interplanetary magnetic field (IMF) is based on proxies derived from geomagnetic indices. The reliability of these proxies is dependent on the homogeneity of magnetic field data. In this paper, we study the interhourly (IHV) and interdiurnal (IDV1d) variability indices calculated from the data of two British observatories, Eskdalemuir and Lerwick, and compare them to the corresponding indices of the German Nieme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The IDV and IDV(1d) indices were discussed in the last section. Note that recently Holappa and Mursula (2015) have suggested that errors in the geomagnetic data make the To relate OSF to sunspot numbers, in this section we use the model of Solanki et al (2000), based on the continuity equation for OSF:…”
Section: Test Using Osf Derived From Geomagnetic Indices and A Contin...mentioning
confidence: 99%
“…The IDV and IDV(1d) indices were discussed in the last section. Note that recently Holappa and Mursula (2015) have suggested that errors in the geomagnetic data make the To relate OSF to sunspot numbers, in this section we use the model of Solanki et al (2000), based on the continuity equation for OSF:…”
Section: Test Using Osf Derived From Geomagnetic Indices and A Contin...mentioning
confidence: 99%
“…However the insight of Svalgaard and Cliver (2005) is very valuable and Rouillard et al (2009) exploited it to reconstruct both B and V SW , and Lockwood (2014a) used 4 different pairings of indices to derive both with an uncertainty analysis back to 1845. There is always the possibility of calibration drift in the historic geomagnetic data (Svalgaard, 2014;Holappa and Mursula, 2015), some of these have been identified, agreed upon and corrected for (e.g. Lockwood et al, 2014d ) whereas others are still debated, and others noted but their effects not properly accounted for.…”
Section: From Geomagnetic Datamentioning
confidence: 99%
“…The IDV and IDV(1d) indices were discussed in the last section. We note that recently Holappa and Mursula (2015) have suggested that errors in the geomagnetic data make the reconstructions greatly in error. However, Lockwood, Owens, and Barnard (2016) point out that Holappa and Mursula introduced errors by calibration against unreliable data, which they then exacerbated by using a less sophisticated and robust reconstruction procedure than that used by Lockwood et al To relate OSF to sunspot numbers, in this section we use the model of Solanki, Schüssler, and Fligge (2000), based on the continuity equation for OSF:…”
Section: Test Using Osf Derived From Geomagnetic Indices and A Continmentioning
confidence: 81%